Kearifan Lokal dalam Pemerintahan: Studi Kasus Lembaga Adat Karampuang - Reski Ramadani Syam; Rasyid Thaha; Suhardiman Syamsu (Fakultas Teknik Universitas Cenderawasih, 2026)
This study was conducted to analyze the role of customary institutions in the government system in Karampuang, as well as to analyze the challenges faced by customary institutions in Karampuang. This study emphasizes the strategic role of customary institutions in the preservation of culture and management of natural resources of indigenous communities in Karampuang. The research method used is a qualitative method through a literature review to collect and analyze information related to the role of customary institutions in the Karampuang customary village. Sources used include the collection of literature such as books, journals, articles, and related documents. The results of the study are expected to provide insight related to the strategic role of customary institutions in the government system. The results of this study indicate that customary institutions in Karampuang play a dual role as pillars of culture and as important institutions in the local government structure, maintaining a balance between cultural values ​​and government administration. However, these customary institutions face many challenges, including legal recognition that must be fought for officially, the threat of confiscation of living space that threatens the sovereignty of customary territories, and the need to strengthen institutional capacity to develop amidst social dynamics and the pressures of modernization.